Identification of a Hyperparasitic Simplicillium obclavatum Strain Affecting the Infection Dynamics of Puccinia striiformis f. sp. tritici on Wheat - Wang, Ning; Fan, Xin; Zhang, Shan; Liu, Bo; He, Mengying; Chen, Xianming; Tang, Chunlei; Kang, Zhensheng; Wang, Xiaojie (Frontiers in Microbiology, 2020)
Wheat stripe rust, caused by Puccinia striiformis f. sp. tritici (Pst), is one of the most serious threats to wheat production worldwide. Changes of Pst virulence may circumvent resistance in wheat varieties, and application of fungicides may cause environmental problems. Parasites of Pst can be used to develop biological agents for environmentally friendly control of this fungal disease. Here, we report a hyperparasitic fungus isolated from Pst and identified it as Simplicillium obclavatum through molecular and morphological characterizations. We demonstrated that inoculation of Pst-infected wheat leaves with S. obclavatum reduced the production and germination rate of Pst urediniospores. Therefore, S. obclavatum has the potential to be developed into a biological control agent for managing wheat stripe rust.